3DJPi: an open-source web-based 3D simulator for Pololu's 3Pi platform - Maggi, Lucas; Teixeira, João Marcelo; Fonseca, José Roberto; Cajueiro, João; Lima, Pedro Vitor; Bezerra, Maria Helena; Melo, Guilherme (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2019)
Line-following robots can recognize and follow a line drawn on a surface. Their operating principles have elements that could be used in the development of numerous autonomous technologies, with applications in education and industry. This class of robots usually represent the first contact students have with educational robotics, being used to develop students’ logic thinking and programming skills. The cost of robotic platforms is still prohibitive in low-budget schools and universities, which makes almost impossible having a platform for each small group of students in a classroom, harming the learning process. This work proposes a 3D web-based open-source simulator for Pololu’s 3Pi line-following robots, making such technology more accessible and available even for distance learning courses. The developed software simulates the robot’s physical structure, behavior, and operations – as being able to read surfaces –, enabling the user to observe the robot following the line as the code commands. The simulator was validated based on experiments that included motion analysis and time measurements of pre-stablished tasks so that its execution could be more coherently based on what happens in reality.